Language corrections and language ideologies in Israeli Hebrew-speaking classes. (4th July 2018) - Netz, Hadar; Yitzhaki, Dafna; Lefstein, Adam
ABSTRACT: This article is about language corrections in Israeli Hebrew-speaking primary classrooms. The ideological significance of language corrections, particularly within the highly contested context of Israeli society and Modern Hebrew, underlies the current study. Teachers in Israeli, Hebrew-speaking classes were found to frequently correct not only their students' language, but also their own. Furthermore, teachers use language corrections not only for instructional purposes (i.e. modeling standard or super-standard language), but also for regulatory purposes (i.e. emphasizing their authority when managing behavior). Interestingly, in contrast to previous studies, we did not encounter explicit student resistance to teacher corrections, indicating Hebrew-speaking students' internalization and acceptance of the standard language ideology. Teachers' self- and other-corrections, as well as the metalinguistic comments accompanying these corrections, likewise reveal a monolithic language ideology, bearing significant pedagogical implications.